The manga guide to statistics - Takahashi, Shin (No Starch Press, 2008)
Think you can't have fun learning statistics? Think again. The Manga Guide to Statistics will teach you everything you need to know about this essential discipline, while entertaining you at the same time. With its unique combination of Japanese-style comics called manga and serious educational content, the EduManga format is already a hit in Japan. In The Manga Guide to Statistics, our heroine Rui is determined to learn about statistics to impress the dreamy Mr. Igarashi and begs her father for a tutor. Soon she's spending her Saturdays with geeky, bespectacled Mr. Yamamoto, who patiently teac.